Quasicrystal as a Reinforcement Material in Magnesium Alloys - Chang, Hye Jung; Kim, Won Tae; Kim, Do Hyang (WILEY-V C H VERLAG GMBH, 2011)
The existence of the two-phase region (icosahedral phase (I-phase) + a-Mg) in the Mg-rich corner of the Mg-Zn-Y system indicates that composites consisting of I-phase and ductile a-Mg can be fabricated by a simple solidification process. Alloys with a range of combined strength and ductility can be designed by changing the fraction of the I-phase. Strengthening in proportion with increasing the volume fraction of I-phase can be explained by the effect of dispersion hardening due to the presence of finely dispersed I-phase particles. When quasicrystals exist in the a-Mg matrix as a second phase in Mg-Zn-Y alloys, the quasicrystals are stable against coarsening during thermomechanical processes such as hot rolling and high-temperature forming, due to the low interfacial energy of the quasicrystals with the a-Mg crystalline matrix, which provides strong bonding properties at the I-phase/matrix interface. Therefore, quasicrystal-reinforced Mg-Zn-Y alloys exhibit a much better combination of mechanical properties and formability than commercially used alloys such as AZ31 and AZ 61.
Keywords: ICOSAHEDRAL PHASE; MECHANICAL-PROPERTIES; DEFORMATION-BEHAVIOR; GRAIN-SIZE; MG; AL; MICROSTRUCTURE; TEMPERATURE; DIAGRAM; FE